KONSTRUKTIVISME: DAMPAK PELEMAHAN KONSTITUSI TERHADAP PEMERINTAH, STUDI KASUS KPK RI - Chairussani Abbas Sopamena (Universitas Jenderal Ahmad Yani, 2024)
This research examines the impact of the weakening of the Corruption Eradication Commission (KPK) on the credibility of the Indonesian government in the context of international relations. Using a constructivist perspective, this study analyzes how the revision of the KPK Law in 2019 and other weakening efforts have affected the social construction of Indonesia's identity as a country committed to eradicating corruption. The research shows that the weakening of the KPK has significantly impacted the decline in corruption enforcement performance, as reflected in the decrease in the number of sting operations and the slowdown in investigation processes. This has resulted in a decline in public trust and Indonesia's Corruption Perception Index score. The impact of the KPK's weakening is also evident in the investment climate, where foreign investors are beginning to doubt Indonesia's commitment to combating corruption. Moreover, Indonesia's position in bilateral and multilateral cooperation, as well as in international forums such as the G20 and APEC, has also been negatively affected. This study concludes that to reconstruct its credibility, the Indonesian government needs to undertake comprehensive efforts involving regulatory reform, human resource development, strengthening of anti-corruption institutions, and effective public diplomacy. This research contributes to the understanding of the importance of strong anti-corruption institutions in building and maintaining government credibility in the international arena.